Uma educação para altertranscender-ser: a empatia como fundamento pedagógico para o ensino religioso - Castro, Evanor Daniel de (2011)
As the concerning concepts responsability and self care, according to Donald Woods Winnicott was concepted an empathic alterity at the religious pedagogical environment . The praxis of this alterity was set as propicious to establish a good enough environment among students and the professional of the religious curricular teaching component. This alterity creates a safe, cosy and confident environment that establish a proper environment for creativity and autonomy of individuals. Based on psicanalitic studies of Winnicott and Ana-Maria Rizzuto, there are signals that this praxis reinforces situations of caring lived in early childhood, as , praise or faint the images of the transcendent, that are reflexes of caring experiences with paternal providers.Finally, it proposes a practice that make sense to what the professional of the religious teaching represents at the classroom, in the contents proposed by the national curricular plans to the religious teaching. This coherent epistemological position would assure the imagination, criativity and independence of the students. It would be the encounter of their limitations and the others limitations.As the docent creates a favorable environment for learning through concerning, reception and empathy, the religious teaching professional promotes a rescue of the non-care moments that occurs in the history of students which allows their agressivity would be received and canalized through creativity. It is destroying the no- me that the I am shows up. In the destruction must have the survival of the carer, so that he will be recognized as someone who offers love.Through this attitude the person is able to feel guilty before destruction, so that he is able to retribute love for those who love him.This experience must be lived in the classroom for those who have a history of affective needing.The ―survival‖ of the docent allows others to learn how to take care of themselves and how to establish their own limits. It allows people to encounter their limits and the limits of others. When it finally happens the others become a bridge for transcendence.The act of concerning for the others allows stimulates a more solidary and fair society.This empatic capacity brings the transcendence that comes from the other.Hence, altertranscendence means caring and recognition to the other, the solidarity and the approaching of human´s finitude as a presupposition for fraternity. Therefore themes in different religious culture that may be analized in the classroom as a vision of a new social reality, as a spot to imagine and be different. To summarize, the altertranscendence brings the individual autonomy through the other, through the capacity of being responsible.